2018
DOI: 10.1016/j.neuro.2018.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivity and memory/learning deficits evoked by developmental exposure to nicotine and/or ethanol are mitigated by cAMP and cGMP signaling cascades activation

Abstract: Pregnant smoking women are frequently episodic drinkers. Here, we investigated whether ethanol exposure restricted to the brain growth spurt period when combined with chronic developmental exposure to nicotine aggravates memory/learning deficits and hyperactivity, and associated cAMP and cGMP signaling disruption. To further investigate the role of these signaling cascades, we verified whether vinpocetine (a phosphodiesterase inhibitor) ameliorates the neurochemical and behavioral outcomes. Swiss mice had free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 75 publications
0
10
0
Order By: Relevance
“…Vinpocetine was suspended in 0.5% w/v carboxymethylcellulose (CMC) and was administered orally with the help of oral gavage in two doses (10 mg.kg À1 and 20 mg.kg À1 ; p.o.) (Abreu-Villaça et al, 2018;Guly as, Halldin, S ov ag o, et al, 2002;Ishola et al, 2018;Shibota et al, 1982).…”
Section: Drugsmentioning
confidence: 99%
See 2 more Smart Citations
“…Vinpocetine was suspended in 0.5% w/v carboxymethylcellulose (CMC) and was administered orally with the help of oral gavage in two doses (10 mg.kg À1 and 20 mg.kg À1 ; p.o.) (Abreu-Villaça et al, 2018;Guly as, Halldin, S ov ag o, et al, 2002;Ishola et al, 2018;Shibota et al, 1982).…”
Section: Drugsmentioning
confidence: 99%
“…In line with these observations, in our study vinpocetine administration resulted in amelioration of behavioral deficits produced by prenatal exposure to VPA. Vinpocetine is known to improve cAMP and cGMP levels and their common downstream component pCREB levels via the cAMP/CREB and PKG pathway in both cerebral cortex and hippocampus, areas of brain indicated to play a major role in locomotor activity (Abreu-Villaça et al, 2018). As impairments in social behavior and stereotypical behavior have previously been linked with reduced expression of synapsins (Provenzano et al, 2015), pCREB, BDNF (Xu et al, 2019) and DCX (Stephenson et al, 2011) in rodents.…”
Section: Notementioning
confidence: 99%
See 1 more Smart Citation
“…In utero exposure to alcohol resulted in development of ADHD‐associated abnormalities in behaviour and biochemical markers of neuronal health possibly via the suppression of cAMP/pCREB pathway (Abreu‐Villaça et al., 2018; Nunes et al., 2011). It is widely accepted that the low central levels of pCREB and BDNF are associated with PAE in models of foetal alcohol syndrome (Caldwell et al., 2008; Mahabir et al., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the brain growth spurt period occurs during the third trimester of gestation when ethanol consumption frequently occurs (Ethen et al., 2009). Animal studies indicate that ethanol exposure during the brain growth spurt period evokes locomotor hyperactivity and learning and memory deficits, which are typical adverse behavioral outcomes of FASD (Abreu‐Villaça et al., 2018; Cristina‐Rodrigues et al., 2020; Filgueiras, Krahe, & Medina, 2010; Nunes et al., 2011). We recently reported that ethanol exposure during the brain growth spurt period impairs social behavior in adolescent males (Demarque et al., 2020).…”
Section: Introductionmentioning
confidence: 99%